Young infant clinical signs study, Pakistan: a data note [version 1; peer review: 2 approved] - Fyezah Jehan; Shiyam Sunder Tikmani; Shahira Shahid; Anita K.M. Zaidi; Nick Brown; Muhammad Imran Nisar (Gates Open Research, 2021)
Neonatal sepsis is the leading cause of child death globally with most of these deaths occurring in the first week of life.  It is of utmost public health importance that clinical signs predictive of severe illness and need for referral are identified early in the course of illness. From 2002-2005, a multi country trial called the Young Infant Clinical Signs Study (YICSS) was conducted in seven sites across three South-Asian (Bangladesh, India, and Pakistan), two African (Ghana, and South Africa), and one South American (Bolivia) country. The study aimed to develop a simplified algorithm to be used by primary healthcare workers for the identification of sick young infants needing prompt referral and treatment. The main study enrolled 8,889 young infants between the ages of 0-59 days old. This dataset contains observations on 2950 young infants aged 0-59 days from the Pakistan site. The data was collected between 2003-2004 with information on the most prevalent signs and symptoms. The data from this study was used to update the Integrated Management of Childhood Illness guidelines. The World Health Organisation (WHO) seven-sign algorithm has been used in other major community-based trials to study possible serious bacterial infection and its treatment regimens.